Health Risks of Exposure to Cadmium in Tila Fish in The Community of Kerta Buana Village, Kutai Kartanegara District - Suhelmi, Reni; Hansen, Hansen; Putri Nurislam, Ramadhani (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
The presence of heavy metal cadmium in ex-mining ponds results from coal excavation and refining activities. Ex-mining ponds are used by the community for fishing and fish farming, the community uses ex-mining ponds. Communities often consume fish without fully understanding its quality and the potential health risks it poses. As a result, it is necessary to conduct community research on environmental health risk analysis (EHRA) as a first step to estimating or predicting health risks. The research was conducted for one month, from June to July 2022. Data collection was carried out using questionnaires, food models, and anthropometric measurements. Fish samples were collected from five different locations in ex-mining ponds, while human samples were taken from 20 respondents. The analysis of cadmium concentration in fish was done using the Atomic Absorption Spectrophotometry (AAS) method. The study's results showed that the highest number of samples was about 0.0006 mg/kg of cadmium, while all of the respondents had a risk level value (RQ) of less than 1. This indicates that none of the respondents faced any health risks. It is recommended that people know and pay more attention to the types and sources of fish produced.